2020
DOI: 10.3390/ma13081823
|View full text |Cite
|
Sign up to set email alerts
|

Application of Electrically Conducting Nanocomposite Material Polythiophene@NiO/Frt/GOx as Anode for Enzymatic Biofuel Cells

Abstract: In this work, nano-inspired nickel oxide nanoparticles (NiO) and polythiophene (Pth) modified bioanode was prepared for biofuel cell applications. The chemically prepared nickel oxide nanoparticles and its composite with polythiophene were characterized for elemental composition and microscopic characterization while using scanning electron microscopy. The electrochemical characterizations of polythiophene@NiO composite, biocompatible mediator ferritin (Frt) and glucose oxidase (GOx) catalyst modified glassy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…This is because the FAD cofactor that is buried deep within the protein shell is not easily inactivated. However, due to the deep location of the active site of the enzyme and the long tunneling time due to the macromolecular structure of the enzyme, it is difficult to transfer electrons on the electrode surface [ 46 ]. After material modification on the electrode surface, DET can be achieved through electron tunneling between the enzyme and the electrode.…”
Section: Enzyme Biofuel Cellsmentioning
confidence: 99%
“…This is because the FAD cofactor that is buried deep within the protein shell is not easily inactivated. However, due to the deep location of the active site of the enzyme and the long tunneling time due to the macromolecular structure of the enzyme, it is difficult to transfer electrons on the electrode surface [ 46 ]. After material modification on the electrode surface, DET can be achieved through electron tunneling between the enzyme and the electrode.…”
Section: Enzyme Biofuel Cellsmentioning
confidence: 99%
“…But enzymes are buried inside the material, making it difficult to transfer electrons outward. Bioanodes with nanonickel oxide (NiO) nanoparticles and polythiophene (Pth) modification can improve the performance of EBFC. The Pth@NiO/Frt/GOx bianode with ferritin (Frt) had a current density of 5.4 mA cm –2 and an ET rate of 2.0 s –1 .…”
Section: Introductionmentioning
confidence: 99%
“…Using renewable power associated with glucose as the molecule also provides sustainability, and sources offer eco-friendliness [ 8 , 9 ]. Recently, it has been observed that using nanoparticles with conducting polymers can improve the performance of biofuel cells [ 10 , 11 ]. In a study by Saurabh Kumar et al, it was observed that when iron oxide nanoparticles are combined with poly (3,4-ethylene dioxythiophene): poly (styrene sulfonate) and used as the electrode, the electrochemical output and the stability of signal of the cancer biosensor were enhanced [ 12 ].…”
Section: Introductionmentioning
confidence: 99%